2002
DOI: 10.1128/aem.68.7.3261-3269.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Production and Characterization of a Fibrin-Specific Single-Chain Antibody Fragment fromBacillus subtilis: Effects of Molecular Chaperones and a Wall-Bound Protease on Antibody Fragment Production

Abstract: To develop an ideal blood clot imaging and targeting agent, a single-chain antibody (SCA) fragment based on a fibrin-specific monoclonal antibody, MH-1, was constructed and produced via secretion from Bacillus subtilis. Through a systematic study involving a series of B. subtilis strains, insufficient intracellular and extracytoplasmic molecular chaperones and high sensitivity to wall-bound protease (WprA) were believed to be the major factors that lead to poor production of MH-1 SCA. Intracellular and extracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(116 citation statements)
references
References 47 publications
0
115
0
1
Order By: Relevance
“…subtilis is able to secrete several proteins up to 20 g l −1 (Schallmey et al, 2004), however it is know that secretion of heterologous proteins in B. subtilis is usually lower (Li et al, 2004). A frequently encountered problem with expression and secretion of heterologous proteins in B. subtilis is the rapid degradation of the secreted protein by extracellular proteases (Wu et al, 2002). It has also been reported that ␤-toxoid is sensitive to protease activity (Hunter et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…subtilis is able to secrete several proteins up to 20 g l −1 (Schallmey et al, 2004), however it is know that secretion of heterologous proteins in B. subtilis is usually lower (Li et al, 2004). A frequently encountered problem with expression and secretion of heterologous proteins in B. subtilis is the rapid degradation of the secreted protein by extracellular proteases (Wu et al, 2002). It has also been reported that ␤-toxoid is sensitive to protease activity (Hunter et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that ␤-toxoid is degraded when in it is secreted into the medium. To test this, the expression cassette was integrated in the amyE locus of a B. subtilis strain WB700 in which seven of the major extracellular proteases are deleted (Wu et al, 2002). In this strain, secreted ␤-toxoid was detected in the medium at concentrations of 0.1-0.5 g ml −1 culture.…”
Section: β-Toxoid Production In B Subtilismentioning
confidence: 99%
“…• Development of expression systems able to drive gene expression under stress conditions • Co-administration of mucosal adjuvants either for biotechnological or biochemical applications (Simonen and Palva 1993, Udaka et al 1989, Udaka and Yamagata 1993, Wang et al 1988, Wong 1995, Wu et al 2002, Wu and Wong 1999. Strong promoters with tightly regulated activity, as those induced by xylose or IPTG, are available for B. subtilis and some of them have already been tested for expression of heterologous or endogenous proteins either as intracellular or secreted proteins (Conrad et al 1996, Kim et al 1996.…”
Section: Improving the Use Of B Subtilis In Vaccine Developmentmentioning
confidence: 99%
“…Strong promoters with tightly regulated activity, as those induced by xylose or IPTG, are available for B. subtilis and some of them have already been tested for expression of heterologous or endogenous proteins either as intracellular or secreted proteins (Conrad et al 1996, Kim et al 1996. Similarly, B. subtilis strains unable to secrete several proteases have been shown to reduce degradation of secreted heterologous proteins to trace levels, as compared to the previously used laboratory strains, and can be used as more appropriate hosts for the production of vaccine antigens (Wu et al 1991(Wu et al , 2002.…”
Section: Improving the Use Of B Subtilis In Vaccine Developmentmentioning
confidence: 99%
See 1 more Smart Citation